L’Espagne recherchée et ressentie de Bartolomé Bennassar - François Zumbiehl (Les Cahiers de Framespa)
Spain, with its several ages and aspects, has been an preeminent target for Bartolomé Bennassar’s investigations. For these, he applied at a rather significant level all the traditional instruments and qualities which are expected in any prominent historian. He also used other skills thanks to his great intellectual curiosity and the acuity of his perceptions and emotions. The observation of the actual reality, the cultural anthropology, the well-reasoned contemplation of art works, including his fondness for bullfighting enriched his valuable contribution to the history of Spain and Spanish peoples. Nevertheless this country, this culture and its people’s lifestyle were not just for Bennassar an object of study exclusively turned to the past. They were the opportunity of a personal encounter with values and feelings that enriched his specific way of life and his way of thinking.